2012
DOI: 10.1016/j.str.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Internally Deleted Human tRNA Synthetase Suggests Evolutionary Pressure for Repurposing

Abstract: SUMMARY Aminoacyl-tRNA synthetases (AARSs) catalyze aminoacylation of tRNAs in the cytoplasm. Surprisingly, AARSs also have critical extracellular and nuclear functions. Evolutionary pressure for new functions might be manifested by splice variants that skip only an internal catalytic domain (CD) and link non-catalytic N- and C-terminal polypeptides. Using disease-associated histidyl-tRNA synthetase (HisRS) as an example, we discovered an expressed 171 amino acid protein (HisRSΔCD) that deleted the entire CD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 31 publications
(38 reference statements)
2
36
0
Order By: Relevance
“…Interestingly, the first 60 aa of HisRS are encoded by the first two exons of the mRNA of HARS and are absent from HisRSs of prokaryotes and lower eukaryotes. As expected, anti-Jo-1 Abs do not react with Escherichia coli HisRS (9). According to our structural analysis, this small domain (designated as a WHEP domain) forms a helical coiled-coil structure (9).…”
Section: Idiopathic Inflammatory Myositis (Iim)supporting
confidence: 78%
See 4 more Smart Citations
“…Interestingly, the first 60 aa of HisRS are encoded by the first two exons of the mRNA of HARS and are absent from HisRSs of prokaryotes and lower eukaryotes. As expected, anti-Jo-1 Abs do not react with Escherichia coli HisRS (9). According to our structural analysis, this small domain (designated as a WHEP domain) forms a helical coiled-coil structure (9).…”
Section: Idiopathic Inflammatory Myositis (Iim)supporting
confidence: 78%
“…As expected, anti-Jo-1 Abs do not react with Escherichia coli HisRS (9). According to our structural analysis, this small domain (designated as a WHEP domain) forms a helical coiled-coil structure (9). Other work showed that HisRS(1-48) induced migration of CD4 ϩ and CD8 ϩ lymphocytes, IL-2-activated monocytes, and immature dendritic cells.…”
Section: Idiopathic Inflammatory Myositis (Iim)supporting
confidence: 77%
See 3 more Smart Citations